Consumer Protection in Health Services: A Normative Analysis Of Patient Rights In Medical Malpractice Cases - Baskoro Tri Pamungkas; Rizki Maulana Ahzar; Alvian Tresna Chariza (IHSA Institute, 2025)
Medical malpractice is a legal issue that positions patients as a vulnerable party susceptible to harm due to the istakes or negligence of medical personnel. This research employs a normative juridical method to examine the implementation of consumer protection priciples from Law No 8 of 1999 to cases of medical malpractice, as well as the dispute resolution mechanisms under Law No. 17 of 2023 concerning Health. Patients are positioned as consumers of health services who possess fundamental rights, such as the right to receive accurate information, safe services, and compensation in the event of negligence. Protection is afforded through preventive measures in the form of professional supervision and development, as well as repressive measures through criminal, civil, or ethical channels. The Health Law provides a tiered dispute resolution mechanism, commencing with mediation, familial settlement, examination by a Disciplinary Council, and litigation if necessary. The affirmation of the le.gal responsibility of medical personnel and the obligation for providers to pay compensation establishes consumer protection as a crucial framework for ensuring patient safety and enhancing the accountibility of health services